Reprodução camponesa em área de assentamento na Amazônia: um estudo no Assentamento João Batista II, Castanhal - Pará - GUILHERME JÚNIOR, José Antônio (Universidade Federal do Pará, 2017)
Our research focuses on the peasant reproduction in a rural area in the Amazon. The João Batista II settlement, localized in the city of Fortaleza Pará state, was elected as a case study, being the oldest settlement organized by the Movement of Landless Rural Workers in the middle region of the northeastern Pará. The general objective of this research is to analyze the peasant reproduction in the Amazon, understanding that this process happens in the construction of the territory. To better structure our research it were chosen the variables: production activities and social organization, understanding them as part of actions that make up the peasent reproduction. Aspects such as: debt, natural poor soil, commercialization difficulties and political disputes within the settlement, have been constituted as factors that limits the sociospatial peasent reproduction in settlement João Batista II.